Exploring the Strategies of Raising Motivation among ESL students in a non-English speaking context - Marina Aiusheeva; Laode Muhammad Firman Guntur (ELS Journal on Interdisciplinary Studies in Humanities, 2019)
Motivation, undoubtedly, plays a very crucial role in any learning process including second and foreign language learning. Such cruciality positions the maintaining and motivation raising in the integral part of learning and more so in the currently growing and more technologically advanced learning environments. This paper conceptually discussed the motivation raising strategies which have been employed toward English as second language (ESL) learners in two different dimensions, which are those strategies which depend on the role of an ESL teacher (i.e. pedagogical and material selection) and those which do not (i.e. parents, school institutions, media, and gender difference). Despite the existence of other external factors, we argue that teacher plays the decisive role on ESL learners’ motivation. From the critical review and more extended discussion, it is found that teacher’s awareness toward the cruciality of students’ motivation influences the strategies used by the teachers in order to raise motivation. The paper also re-emphasises the urgent needs for a more learner-centred learning as it is believed to have positive impact for learners’ motivation. This paper concludes by highlighting the significant contributions of the insights discussed within this study, especially for ESL teaching practitioners.